Dose adjustment of biologic therapies for psoriasis in dermatological practice: a retrospective study. (27th February 2017) - Esposito, M.; Gisondi, P.; Conti, A.; Giunta, A.; del Giglio, M.; Di Mercurio, M.; Veneziano, L.; Ferrucci, G.; Bianchi, L.; Chimenti, S.; Girolomoni, G.
Abstract: Introduction: Despite the large routine use of biologic drugs in psoriasis treatment, the majority of studies do not take into consideration dose‐adjustment practice in 'real‐life' dermatological setting. In routine clinical practice, the disease management may include a large number of conditions requiring non‐standard dosage regimens, including dose escalation, dose reduction and/or off‐label treatment interruption. Objective: The ONDA (Outcome of non‐standard dosing regimen in Psoriasis and Psoriatic Arthritis) study aim was to retrospectively analyse dose‐adjustment strategies among biologic therapies for psoriasis in dermatological practice during a 3‐year period. Results: This retrospective, observational, multicentre study was carried out in 350 patients (68% male, 32% female) affected by plaque‐type psoriasis (Pso) with a coexistence of psoriatic arthritis in 164 patients (46.9%). At baseline mean PASI score was 14.9 (SD 7.2). Dose adjustment was demonstrated to be a common practice with 70/350 patients (20%) who needed a dose variation during the treatment time, in particular a dose increase in 20/70 patients (28.6%) and a dose reduction in 50/70 patients (71.4%). Dose increase was due to inefficacy on Pso parameters in 60% of cases and to inefficacy of PsA parameters in 40% of cases, while dose reduction (or temporary off‐label treatment interruption) was due to prolonged remission in 54% of cases, other reason in 18% of cases, patient choice or request in 14% of cases, occurrence of concomitant event in 12% of cases. Conclusion: Dose adjustment is a common clinical practice, consisting of frequent dose reduction when a disease prolonged remission is obtained or dose increase to improve efficacy on Pso and PsA disease parameters.